Effect of Hydraulic Expansion on Arteriovenous Fistula of Hemodialysis Patients - Ren, Wanjun; Du, Yuejuan; Jiang, Huili; Xu, Dongmei (The Thoracic and Cardiovascular Surgeon, 2019)
Background Chronic kidney disease has become a serious public health problem in China. Our study is to explore effect of hydraulic expansion on arteriovenous fistula (AVF) of hemodialysis patients.Methods A total of 190 patients with end-stage renal disease (ESRD) were randomly divided into hydraulic expansion group (n = 117) and conventional surgery group (n = 73). Age, sex, the cause of ESRD, height, weight, body mass index (BMI), blood pressure, and diameter of artery and vein from ultrasonography before surgery from patients were recorded. Doppler ultrasonography of vessel was performed with a 12-MHz scanning probe for vascular measurements. The time of first cannulation was recorded. Primary and secondary patency rates were compared between the two groups.Results The mean arterial pressure for this cohort of patients was around 98.12 mm Hg. The mean diameters of artery and vein ready for anastomoses measured by ultrasonography before surgery were 1.96 and 2.04 mm, respectively. Age, weight, BMI, sex ratio, the cause of renal failure, history of catheter insertion, mean arterial pressure, frequency of hemodialysis, blood flow of hemodialysis, and the mode of anastomoses of AVF in conventional surgery group were similar to hydraulic expansion group. There were no differences in stroke volume of radius arterial and venous pressure before dilation between the two groups. The stroke volume of radius artery increased significantly after hydraulic expansion than before dilation and control group. The primary patency rates of AVF in patients with hydraulic expansion were higher significantly than conventional surgery group. The secondary patency rates in conventional surgery group were not different from hydraulic expansion group.Conclusion Hydraulic expansion showed no difference from conventional surgery in complication after operation, and could decrease the time reliance on catheters and the risk of catheter-related infection, thrombosis, and decrease the related medical care costs.
Keywords: hydraulic expansion; arteriovenous fistula; hemodialysis; end-stage renal disease; patency rate